The impact of digital accounting on the quality of financial reports: A study of a sample of economic institutions - Ghalem, Kamel (International journal of economic perspectives, 2024)
The study dealt with the impact of the application of digital accounting on the quality of the financial reports of the Algerian economic institutions, and aimed to identify the relationship between the application of digital accounting systems and the quality of the financial reports of the Algerian economic institutions through a survey of the opinions of the accounting staff and heads of departments in the economic institutions under study, where a random sample was selected. From 30 people representing accountants, heads of accounts departments, financial managers, auditors, and members of accounting departments mainly, 30 questionnaires were distributed, and 30 questionnaires were retrieved with a recovery rate of 100%, and the SPSS program was used to analyze the questionnaire data. The study reached several results, the most important of which are: Digital accounting systems provided reliable and appropriate information and financial statements that are correct to a large extent compared to traditional accounting systems, which earned this information and financial statements the confidence of users, whether the users were internal or external, and the use of digital accounting information systems reflected positively on the quality of financial reports provided by the system.